Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0271308
|View full text |Cite
|
Sign up to set email alerts
|

Sex-, age-, and organ-dependent improvement of bile acid hydrophobicity by ursodeoxycholic acid treatment: A study using a mouse model with human-like bile acid composition

Abstract: Cyp2a12-/-Cyp2c70-/- double knockout (DKO) mice have a human-like hydrophobic bile acid (BA) composition and show reduced fertility and liver injury. Ursodeoxycholic acid (UDCA) is a hydrophilic and cytoprotective BA used to treat various liver injuries in humans. This study investigated the effects of orally administered UDCA on fertility and liver injury in DKO mice. UDCA treatment prevented abnormal delivery (miscarriage and preterm birth) in pregnant DKO mice, presumably by increasing the hydrophilicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…This was also evident in Cyp2c70 - Cyp2a12 double KO mice, where UDCA feeding improved neonatal viability and was protective in the male and female double KO mice at 6 weeks of age and in male double KO mice at 20 weeks of age. ( 59 ). In contrast, UDCA-treated female Cyp2c70 - Cyp2a12 double KO mice at 20 weeks of age still exhibited significant liver injury, with a greatly elevated hepatic BA content and taurolithocholic acid–enriched hydrophobic BA composition ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also evident in Cyp2c70 - Cyp2a12 double KO mice, where UDCA feeding improved neonatal viability and was protective in the male and female double KO mice at 6 weeks of age and in male double KO mice at 20 weeks of age. ( 59 ). In contrast, UDCA-treated female Cyp2c70 - Cyp2a12 double KO mice at 20 weeks of age still exhibited significant liver injury, with a greatly elevated hepatic BA content and taurolithocholic acid–enriched hydrophobic BA composition ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 59 ). In contrast, UDCA-treated female Cyp2c70 - Cyp2a12 double KO mice at 20 weeks of age still exhibited significant liver injury, with a greatly elevated hepatic BA content and taurolithocholic acid–enriched hydrophobic BA composition ( 59 ). When the steroidal farnesoid X-receptor agonist obeticholic acid was recently evaluated in Cyp2c70 KO mice, short-term 4-weeks treatment did not improve the hepatic fibrosis or development of cholangiopathy, despite suppressing BA synthesis ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…While CA conjugates were conserved in both mouse cecal and human stool extracts, MCA conjugates were not observed in the human FMT samples. 34,35 Hierarchical clustering and PCA for FMT experiments (Figures 5A,B and S9) noted decreased temporal resolution for each sampling period in contrast to the mouse data, though the timespan for FMT sample collection is notably longer (months) versus the mouse model (weeks). Hierarchical clustering results showed that CA and CDCA conjugates are present pre-FMT and depleted in post-FMT, while DCA and related conjugates showed the opposite trend.…”
Section: Abx Treated Mouse Model Cecal Contentmentioning
confidence: 99%
“…Moreover, CDCA is metabolized into muricholic acids in mice which are absent in humans and have different affinities for bile acid receptors compared to CDCA and lithocholic acid, a CDCA-derived secondary bile acid. Knockout mouse models that lack the bile acid metabolizing enzymes Cyp2c70/Cyp2a12 have bile acid pools closer to humans 30, 31 . Future studies utilizing these models could help elucidate the physiological impact of I3A on liver bile acids and their role in fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout mouse models that lack the bile acid metabolizing enzymes Cyp2c70/Cyp2a12 have bile acid pools closer to humans 30,31 . Future studies utilizing these models could help elucidate the physiological impact of I3A on liver bile acids and their role in fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%